EVALUATION OF DIFFERENT TECHNIQUES FOR THE DIFFERENTIATION OF PATHOGENIC AND NON PATHOGENIC STRAINS OF YERSINIA-ENTEROCOLITICA - Bauab, Taís Maria [UNESP]; Corrca, E. F.; Falcao, D. P. (Soc Brasileira Microbiologia, 1995)
Different methods and tests have been used to evaluate the pathogenic potential of distinct Y. enterocolitica serotypes and biotypes. We tested a total of 60 Y. enterocolitica strains, being 25 of human origin (serotype O3 biotype 4 and serotype O5 biotype 1); 6 of animal origin (serotype O3 biotype 4); 19 isolated from the environment (serotype O5.27 biotypes 1 and 2); and 8 isolated from food (serotype O5 biotype 1 and serotype 05.27 biotype 1). The methods used were based on plasmid gene expression (autoagglutination, calcium-dependence at 37 degrees C and Congo Red absorption tests), chromosomal gene expression (assays for pyrazinamidase activity, salicin fermentation and esculin hydrolysis), and invasion of HEp-2 cells. All but one of the Y. enterocolitica O3 strains, were found to be potentially pathogenic when submitted to the pyrazinamidase-salicin-esculin tests. In contrast, the results obtained with the assays related to plasmidial gene expression were not so uniform, probably due to plasmid loss. The least homogeneous results were obtained with the HEp-2 cell invasion test. Y. enterocolitica O5 behaved in a uniform manner when tested with the first two groups of tests (based on chromosomal and plasmidial gene expression), but not when tested with the HEp-2 invasion assay. The strains of serotype O5.27 biotype 1 presented a uniform behavior hen submitted to the chromosomic-related tests, showing no pathogenicity. However, they did not provide conclusive results with the tests related to plasmidial gene expression or HEp-2 cell invasion. We conclude that the tests related to chromosomal gene expression (esculin-salicin-pyrazinamidase) are simple and highly effective for the detection of potentially pathogenic Y. enterocolitica isolated from clinical cases.
Keywords: YERSINIA ENTEROCOLITICA; PATHOGENICITY; ESCULIN HYDROLYSIS; SALICIN FERMENTATION; PYRAZINAMIDASE ACTIVITY